2021
DOI: 10.15252/embj.2020104549
|View full text |Cite
|
Sign up to set email alerts
|

Msps governs acentrosomal microtubule assembly and reactivation of quiescent neural stem cells

Abstract: The ability of stem cells to switch between quiescence and proliferation is crucial for tissue homeostasis and regeneration. Drosophila quiescent neural stem cells (NSCs) extend a primary cellular protrusion from the cell body prior to their reactivation. However, the structure and function of this protrusion are not well established. Here, we show that in the protrusion of quiescent NSCs, microtubules are predominantly acentrosomal and oriented plus‐end‐out toward the tip of the primary protrusion. We have id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…We found that Ace-tub intensity in the protrusion gradually declines over the course of larval development (Figure S1C-F). Msps, an XMAP215/ch-TOG family protein, is a key regulator of microtubule growth in both quiescent and dividing NSCs 33,42 , Interestingly, msps depletion led to significantly lower levels of Ace-Tub in the primary protrusions of qNSCs as compared to control brains at 0h and 6h ALH (Figure S1C-E), and almost similar levels at 16h ALH (Figure S1C and F). This data is consistent with age-dependent decline of the regeneration capability of qNSCs and suggests that the microtubules may play a role in the regeneration of qNSC primary protrusions.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…We found that Ace-tub intensity in the protrusion gradually declines over the course of larval development (Figure S1C-F). Msps, an XMAP215/ch-TOG family protein, is a key regulator of microtubule growth in both quiescent and dividing NSCs 33,42 , Interestingly, msps depletion led to significantly lower levels of Ace-Tub in the primary protrusions of qNSCs as compared to control brains at 0h and 6h ALH (Figure S1C-E), and almost similar levels at 16h ALH (Figure S1C and F). This data is consistent with age-dependent decline of the regeneration capability of qNSCs and suggests that the microtubules may play a role in the regeneration of qNSC primary protrusions.…”
Section: Resultsmentioning
confidence: 93%
“…In most dividing cells, including active NSCs, the centrosomes function as the microtubule-organizing centre (MTOC), the major site of microtubule nucleation and anchoring and the central point for the formation of microtubule arrays 31,32 . Interestingly, a recent study from our lab has demonstrated that microtubules in the primary protrusion of qNSCs are predominantly acentrosomal and oriented plus-end-out, distal to the cell body 33 . However, the microtubule-organizing centre of qNSCs is still unknown.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations